Perancangan Media Digital Sebagai Strategi Promosi Penerimaan Peserta Didik Baru (PPDB) Pada Era Modern - Depari, Andi Sahputra; Hijriah, Hijriah; Putri, Hesti Rosita Dwi (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2024)
The mentoring or training activities for designing digital media to promote the admission of new students (PPDB) represent a successful collaboration between teaching staff of the Kalimantan Institute of Technology with the KPS National School in Balikpapan. This training involves teams of lecturers, students, and the KPS National School in Balikpapan, who are provided with a deep understanding of the concepts and strategies involved in designing digital media to promote PPDB. In a collaborative atmosphere, participants actively engage in discussions and practical exercises to design digital media. The success of these activities is reflected in the high level of participation and concrete results, expected to enhance the visibility and attractiveness of schools to prospective students and the general public, thereby supporting the long-term growth of educational institutions.